RAPD based molecular analysis genetic diversity of Ornithoptera croesus found in Bacan Island, Indonesia - ABDU MAS'UD; A.D COREBIMA; MOHAMMAD AMIN; FATCHUR ROHMAN (Society for Indonesian Biodiversity, 2018)
Mas'ud A, Corebima AD, Amin M, Rohman F. 2018. RAPD based molecular analysis genetic diversity of Ornithoptera croesus found in Bacan Island, Indonesia. Biodiversitas 19: 1273-1279. The endemic butterfly commonly known as birdwing butterfly found in Bacan island (Ornithoptera croesus) was first discovered by Wallace in 1859. The O. croesus hotspot is a nature preserve located at various altitudes around Sibela mountain. The O. croesus belongs to macrolepidoptera which is famous for their variety of body colors and typical morphology identified in female and male found at various altitude places. This study aimed to examine the genetic diversity of O. croesus at some different altitude spots in Sibela mountain using PCR-RAPD molecular analysis. The result of the DNA amplification showed high polymorphism in O. croesus (84,81). The clustering pattern indicated that O. croesus ? 400 meters above sea level (m asl.) and O. croesus ? 400 m asl. had the highest level of genetic similarity, while the lowest level of genetic similarity was observed in O. croesus ? 800 m asl. and O. croesus ? 20 m asl. On the basis of these findings, clustering pattern showed that the highest level similarity could also be found in species that live in the same altitude.